Dual Amperometric Immunosensor for Improving Cancer Metastasis Detection by the Simultaneous Determination of Extracellular and Soluble Circulating Fraction of Emerging Metastatic Biomarkers. Issue 4 (1st October 2019) - Valverde, Alejandro; ben Hassine, Amira; Serafín, Verónica; Muñoz‐San Martín, Cristina; Pedrero, María; Garranzo‐Asensio, María; Gamella, Maria; Raouafi, Noureddine; Barderas, Rodrigo; Yáñez‐Sedeño, Paloma; Campuzano, Susana; Pingarrón, José M.
Abstract: This paper reports the development of a dual immunosensor using magnetic microcarriers (MBs) and amperometric transduction at dual screen‐printed carbon electrodes (SPdCEs) for the simultaneous determination of two biomarkers: interleukin‐13 receptor α2 (IL‐13Rα2) and E‐cadherin (E‐CDH), with both extracellular and soluble fraction; oncogenic and tumor suppressor markers, respectively, of great relevance in metastatic processes. The implemented methodology involved the formation of sandwich‐type immunocomplexes using specific capture antibodies immobilized onto carboxylic acid magnetic microbeads (HOOC‐MBs), and biotinylated detector antibodies labeled with streptavidin−horseradish peroxidase conjugates (Strep‐HRP). The amperometric detection was performed by addition of hydrogen peroxide in the presence of hydroquinone (HQ) as the redox mediator. The dual immunosensing platform provided linear calibration ranges suitable for the determination of both biomarkers in liquid and solid clinical specimens as well as excellent selectivity against other cancer biomarkers. This simple handling dual bioplatform was applied to the determination of the soluble and extracellular fraction of the target biomarkers in serum and paraffined‐embedded tissues from colorectal cancer (CRC) patients diagnosed at different tumor grade. The obtained results reveal great potential of this configuration to improve the reliability in diagnosing metastatic CRC. Abstract :